Chiropractic Spinal Manipulation Prevents Secondary Hyperalgesia Induced by Topical Capsaicin in Healthy Individuals - Gevers-Montoro, Carlos; Provencher, Benjamin; Northon, Stéphane; Stedile-Lovatel, João Paulo; Ortega de Mues, Arantxa; Piché, Mathieu (Frontiers in Pain Research, 2021)
Background and Aims: Spinal manipulation (SM) is currently recommended for the management of back pain. Experimental studies indicate that the hypoalgesic mechanisms of SM may rely on inhibition of segmental processes related to temporal summation of pain and, possibly, on central sensitization, although this remains unclear. The aim of this study was to determine whether experimental back pain, secondary hyperalgesia, and pain-related brain activity induced by capsaicin are decreased by segmental SM. Methods: Seventy-three healthy volunteers were randomly allocated to one of four experimental groups: SM at T5 vertebral level (segmental), SM at T9 vertebral level (heterosegmental), placebo intervention at T5 vertebral level, or no intervention. Topical capsaicin was applied to the area of T5 vertebra for 40 minutes. After 20 minutes, the interventions were administered. Pressure pain thresholds (PPTs) were assessed outside the area of capsaicin application at 0 and 40 minutes to examine secondary hyperalgesia. Capsaicin pain intensity and unpleasantness were reported every four minutes. Frontal high-gamma oscillations were also measured with electroencephalography. Results: Pain ratings and brain activity were not significantly different between groups over time (p > 0.5). However, PPTs were significantly decreased in the placebo and control groups (p < 0.01), indicative of secondary hyperalgesia, while no hyperalgesia was observed for groups receiving SM (p = 1.0). This effect was independent of expectations and greater than placebo for segmental (p < 0.01) but not heterosegmental SM (p = 1.0). Conclusions: These results indicate that segmental SM can prevent secondary hyperalgesia, independently of expectations. This has implications for the management of back pain, particularly when central sensitization is involved.